Investigation of Many‐Body Effects in the Quasi‐Two‐Dimensional Electronic System of Organic Charge‐Transfer Salts. Issue 9 (26th April 2019) - Mashoff, Torge; Regel, Johannes; Medjanik, Katerina; Schönhense, Gerd; Huth, Michael; Müller, Jens; Lang, Michael; Valentí, Roser; Baumgarten, Martin; Elmers, Hans‐Joachim
Abstract : This article reviews recent progress in the understanding of many‐body effects in the quasi‐two‐dimensional electronic system of organic charge‐transfer salts using element‐selective X‐ray absorption and scanning tunneling spectroscopy techniques. A few previously unpublished topographical scanning tunneling microscopy images illustrate structural consequences of the charge transfer mechanism. The first part of the review focuses on the understanding of the charge transfer between acceptor and donor molecules in general. Results for dithiophene‐based organic semiconductors as a representative model system is reviewed that is relevant for electronic applications, too. Experimental results are used to develop appropriate calculation schemes with large predictive power. The combination of experiment and theory reveals a charge transfer mechanism that is more complex than just the interaction of single HOMO and LUMO states in donor and acceptor molecules. The second part of the review highlights the emergence of superconductivity as a result of the charge transfer leaving strongly correlated and partly occupied electronic states at the Fermi level. The authors review recent experimental results for the κ ‐phase organic superconductors obtained with scanning tunneling spectroscopy and compare the temperature‐dependent local density of states function with theoretical approaches. The superconducting order parameter for κ ‐(ET)2 Cu[N(CN)2 ]Br reveals an eight‐node gap structure resulting from a strongly anisotropic mixed‐symmetry superconducting gap. Abstract : Many‐body effects in the quasi‐two‐dimensional electronic system of organic charge‐transfer salts are investigated using X‐ray absorption and scanning tunneling spectroscopy techniques. The results on κ‐(ET)2 Cu[N(CN)2 ]Br organic crystals reveal the emergence of a strongly anisotropic superconducting gap comprising eight nodes. This is a consequence of the charge transfer leading to partially filled and strongly correlated electronic bands near the Fermi level.